Komunikasi Dialogis Respons Institusi Jaminan Kesehatan Terhadap Keluhan Pengguna di Instagram - Ageng Rara Cindoswari; Putri Rahmania; Michael Jibrael Rorong; Rizka Dwi Amelia (Communicology: Jurnal Ilmu Komunikasi, 2026)
ABSTRACT Introduction: Social media has become the primary channel for public complaints regarding healthcare services; however, there is still a lack of adequate instruments to distinguish between institutional responses that appear dialogic and those that are genuinely dialogic, particularly in the context of Indonesian-language Instagram. Objective: This study analyzes the quality of dialogic communication in BPJS Kesehatan responses to user complaints on Instagram, identifying dominant response patterns and the systemic factors that shape them. Methods: This study employs a qualitative approach with an intrinsic case study design in Batam City. Data were collected through in-depth interviews with eight informants (public relations staff and active users) and analyzed using reflexive thematic analysis and deductive typological coding based on four ethical criteria. Results: The findings show that monologic, pseudo-dialogic, and authentic dialogic patterns coexist, with pseudo-dialogic responses (responses that appear empathetic but do not resolve the core issue) being the most dominant. Conclusion: Dialogic quality is contextual and fluctuating, shaped by internal capacity constraints and structural limitations of the platform, indicating the need to reposition performance metrics of public digital communication from mere popularity toward the fulfillment of substantive ethical criteria. ABSTRAK   Pendahuluan: Media sosial kini menjadi kanal utama keluhan publik terhadap layanan kesehatan, namun belum tersedia instrumen yang memadai untuk membedakan respons institusi yang terlihat dialogis dari yang benar-benar dialogis, khususnya pada konteks Instagram berbahasa Indonesia. Tujuan: Penelitian ini menganalisis kualitas komunikasi dialogis respons BPJS Kesehatan terhadap keluhan pengguna di Instagram, mengidentifikasi pola respons dominan, dan faktor sistemis pembentuknya. Metode: Menggunakan pendekatan kualitatif dengan desain studi kasus intrinsik di Kota Batam, data dikumpulkan melalui wawancara mendalam terhadap delapan informan (tim humas dan pengguna aktif) dan dianalisis melalui reflexive thematic analysis serta pengkodean tipologis deduktif berbasis empat kriteria etis. Hasil penelitian: Hasil menunjukkan pola monologis, dialogis semu, dan dialogis autentik hadir bersamaan, dengan dialogis semu (respons yang tampak empatik namun tidak menyelesaikan substansi masalah) paling dominan. Kesimpulan: Kualitas dialogis bersifat kontekstual dan fluktuatif, ditentukan oleh hambatan kapasitas internal dan struktural platform, sehingga perlu reposisi metrik keberhasilan komunikasi digital institusi publik dari sekadar popularitas menuju pemenuhan kriteria etis substantif.